Efektivitas Komunikasi Terhadap Perkembangan Pekerjaan Karyawan PT. Hagen Amersa Veta - Arisandy, Dessy; Nurzalinda, Lusia (Universitas Pahlawan Tuanku Tambusai, 2025)
interpersonal communication that studies communication between two people is interpersonal communication. Some common goals are about getting to know, relating, influencing, playing and helping. Theoretically, learning intrapersonal communication concerns what is the effectiveness of interpersonal communication, what unites and separates individuals, how to improve and develop relationships. The purpose of this study is to understand the application of Interpersonal Theory to employees of the engineering division of PT. Hagen Amersa Veta. This study uses a field research method with data collection through interviews and observations. The results of this study indicate that interpersonal communication has proven effective in the development of the work of PT. Hagen Amersa Veta employees.